The Effect of Mini Snakes and Ladders Teaching Medium to Improve Students’ Descriptive Writing Skill - Azhar, Sofura; Santoso, Dian Rahma (PROJECT (Professional Journal of English Education), 2025)
This research discusses the use of non-digital teaching media in school without internet access to improve the writing skill of 7th grade junior high school students at one of the junior high schools in Sidoarjo. This study also aims to determine the effect of using the mini Snakes and Ladders as teaching media. Researchers used a quantitative research design with a pre-experimental method that used only one class without using a control class as a comparison for the experimental class. From the final research data obtained, researchers processed it using a paired sample T-test with SPSS. The pre-test and post-test findings provided the data. The results of the paired sample T-test using SPSS indicate that the pre-test and post-test differed significantly. The pre-test’s average score fell short of the 43,15 score required by the Minimum Completeness Criteria (KKM). In the meantime, the KKM indicator was passed with an average post-test score of 78,75. It demonstrates that the score outcomes vary from one another. Compared to the pre-test, the post-test score has a higher mean. T-test results based on the paired sample test showed that the alpha (α) was 0,05 (0,000<0,05) and sig. (2-tailed) was 0.000. This means that Ha has been approved and H0 has been rejected.